2012
DOI: 10.1186/2045-5380-2-20
|View full text |Cite
|
Sign up to set email alerts
|

The role of the amygdala in the pathophysiology of panic disorder: evidence from neuroimaging studies

Abstract: Although the neurobiological mechanisms underlying panic disorder (PD) are not yet clearly understood, increasing amount of evidence from animal and human studies suggests that the amygdala, which plays a pivotal role in neural network of fear and anxiety, has an important role in the pathogenesis of PD. This article aims to (1) review the findings of structural, chemical, and functional neuroimaging studies on PD, (2) relate the amygdala to panic attacks and PD development, (3) discuss the possible causes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 149 publications
1
38
1
4
Order By: Relevance
“…(9) The present results indicate that the increased amygdala volume phenotype is related in part to ACCN2 alleles that are also associated with risk for PD. Although MRI studies of PD have more often found reduced amygdala volume,(26) our results suggest that ACCN2 may contribute to the relative enlargement of the amygdala. Although this finding might appear to be discrepant with prior MRI studies that find reduced amygdala volume among individuals with PD, we note that our findings do not necessarily imply that risk allele carriers with PD should have large amygdalae.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…(9) The present results indicate that the increased amygdala volume phenotype is related in part to ACCN2 alleles that are also associated with risk for PD. Although MRI studies of PD have more often found reduced amygdala volume,(26) our results suggest that ACCN2 may contribute to the relative enlargement of the amygdala. Although this finding might appear to be discrepant with prior MRI studies that find reduced amygdala volume among individuals with PD, we note that our findings do not necessarily imply that risk allele carriers with PD should have large amygdalae.…”
Section: Discussioncontrasting
confidence: 50%
“…(26)Wemmie and colleagues suggest that amygdala activation by fear-inducing stimuli may trigger fear responses by lowering local pH (e.g. by synaptic release of H + and metabolic effects of neural activity).…”
Section: Discussionmentioning
confidence: 99%
“…Located within the medial temporal lobes, the amygdalar complex is composed of discrete but closely related structures, each playing distinct roles in the perception and processing of stimuli, along with the initiation/termination of emotional reactions (Kim et al, 2012) (Fig. 2).…”
Section: The Amygdalar Complexmentioning
confidence: 99%
“…These results align with previous literature. Following the initial animal studies showing the role these regions play in fear, multiple pharmacological and MRI imaging studies have consistently implicated the thalamus and amygdala in anxiety (Davis, 1992) and panic disorder (Kim et al, 2012) in humans. Though the midbrain has been implicated in some studies of panic or other anxiety disorders (Damsa et al, 2009; Mochcovitch et al, 2014; Nikolaus et al, 2010; Pannekoek et al, 2013), this finding has not been consistent across imaging studies.…”
Section: Discussionmentioning
confidence: 99%